America's water risk: Current demand and climate variability. Issue 7 (9th April 2015) - Devineni, Naresh; Lall, Upmanu; Etienne, Elius; Shi, Daniel; Xi, Chen
Abstract A new indicator of drought‐induced water stress is introduced and applied at the county level in the USA. Unlike most existing drought metrics, we directly consider current daily water demands and renewable daily water supply to estimate the potential stress. Water stress indices developed include the Normalized Deficit Cumulated to represent multiyear droughts by computing the maximum cumulative deficit between demand and supply over the study period (1949–2009) and the Normalized Deficit Index representing drought associated with maximum cumulative deficit each year. These water stress indices map directly to storage requirements needed to buffer multiyear and within‐year climate variability and can reveal the dependence on exogenous water transferred by rivers/canals to the area. Future climate change and variability can be also incorporated into this framework to inform climate‐driven drought for additional storage development and potential applications of water trading across counties.